2012
DOI: 10.1179/1743289810y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive inspection of adhesively bonded patch repairs using Lamb waves

Abstract: Life extension of aging aircraft with adhesively bonded repair patches has received significant interest over the last 10-15 years. This repair method has several advantages over riveted patches since it introduces lower stresses in the repaired area and reduces weight. It is a promising repair technique, which can be also applied to composites, where the load transfer paths through mechanical fasteners can cause local damage. However, patch debonding might occur when the structure is loaded, and the damage mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The effect of noise was tested which showed that OA can detect damage even in extremely noisy environments (SNR = 19). However, in the work by Pavlopoulou et al (2012a) OA exhibited a nonmonotonic behavior with the increasing damage which has been further studied and explained in the current work. For that purpose PCA was employed as a well-established technique, through which the drop in the Mahalanobis squared distance was explored even though the damage propagated.…”
Section: Linear Principal Component Analysis (Pca)mentioning
confidence: 78%
See 2 more Smart Citations
“…The effect of noise was tested which showed that OA can detect damage even in extremely noisy environments (SNR = 19). However, in the work by Pavlopoulou et al (2012a) OA exhibited a nonmonotonic behavior with the increasing damage which has been further studied and explained in the current work. For that purpose PCA was employed as a well-established technique, through which the drop in the Mahalanobis squared distance was explored even though the damage propagated.…”
Section: Linear Principal Component Analysis (Pca)mentioning
confidence: 78%
“…As previously investigated by Pavlopoulou et al (2012a) there are certain cases where the introduced damage to the structure is considerable enough to cause a significant signal time shift. This was demonstrated through an OA on an aluminum repaired panel that was subjected to fatigue loading and which identified unexpected behavior which is discussed and explained in the current work.…”
Section: Test Setsmentioning
confidence: 95%
See 1 more Smart Citation
“…Successful applications involve several engineering case studies based on high‐dimensional data sets . However, in complex structures that are subjected to extensive loading, novelty detection methods can potentially give false alarms .…”
Section: Lamb Waves Propagation For Damage Detectionmentioning
confidence: 99%
“…This can occur if the ultimate shear strain of the adhesive is exceeded under loading. Previous research on this subject has utilised novelty detection methods to detect damage when a metallic repaired structure was subjected to cycling loads .…”
Section: Introductionmentioning
confidence: 99%